Pembelajaran Bahasa Arab Menggunakan Buku Ajar “Aku Cinta Bahasa Arab” pada Siswa Kelas 5 SD di Bekasi - Muhamad Nafiz; Mulhendra Mulhendra; Pepen Suhendra (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Textbooks are a crucial aspect of education. The researcher investigated Arabic language learning using the textbook "I Love Arabic" based on observations conducted previously at an elementary school in Bekasi. The study involved 10 students and 1 teacher. Research instruments included interviews, observations, and documents. The results showed that the "I Love Arabic" textbook significantly aided teachers in conducting Arabic language learning activities. Supporting factors for success included relevant curriculum-aligned content, appropriate language aspects, and a focus on the four language skills. However, some limitations of using this textbook were challenging exercises due to insufficient material, extensive vocabulary memorization within a single chapter, and student interest affecting classroom learning dynamics.